Methods of Disposal of Industrial Waste with Harmful Chemicals - Karimova Feruza Sattarovna; Juraeva Umida Bahodir qizi (Genius Journals, 2022)
The problem of environmental protection is complex and global, and the level of pollution with industrial waste has been increasing in recent years. Long-term pollution of the environment with industrial waste leads to environmental degradation and waste disposal is required. It was recommended to use a highly efficient filter with a highefficiency filter to ensure that the amount of pollutants released into the atmosphere does not exceed the allowable amount. The practical application of this equipment has made it possible to reduce the number of pollutants released into the atmosphere and to dispose of trapped industrial waste.
Keywords: Utilization; Industrial Waste; Recycling; Method